Massage with Herbal Oils as a Novel Therapeutic Approach for Cerebral Palsy: A Medical Hypothesis - Mohsen Hajihoseini; Hanieh Tahermohammadi; Babak Daneshfard; Mohammad Saleh Safari; Arian Karimi Rouzbahani (Tehran University of Medical Sciences, 2023)
Cerebral palsy (CP) is a condition resulting from injury to the developing brain. Treatment modalities vary based on symptomatology and may range from physiotherapy to pharmacologic intervention and surgical intervention. Despite the current therapeutic strategies, outcomes remain suboptimal. In light of limited data regarding the therapeutic effects of oil-based massages on neonates with CP, this study aimed to investigate the potential neurological benefits of incorporating herbal oils into massage treatments for these infants. In this investigation, we conducted a thorough exploration of the medicinal herbs described in the paralysis section of medical and pharmaceutical sources in Persian medicine. Subsequently, we conducted an extensive literature review on the neurological effects of oils or essential oils derived from these herbs. Our search was conducted up to 2023 using pertinent keywords such as Pimpenella anisum L., anise, aniseed, Foeniculum vulgare Miller, fennel, Carum carvi L., caraway, Piper nigrum L., pepper, Cinnamomum zeylanicum, cinnamon, Nigella sativa L., black seed, Vitis vinifera L., grape seed, Olea europaea, olive, Rosa damascene, and rose flower. We specifically focused on studies related to neuroprotection, neurology, massage, and cerebral palsy, and obtained relevant information from data sources such as PubMed, Scopus, and Google Scholar. Our investigation revealed that massage therapy has an impact on CP and that herbal oils possess neurological properties, such as anticonvulsant and neuroprotective effects, as well as enhancements in behavior, memory, learning, and cerebral function. Based on the advantageous mechanisms of action of herbal oils, we postulate that massage therapy utilizing herbal oils may offer a promising complementary approach in the management of newborns with CP. We recommend further experimental and clinical studies to establish their effectiveness.